Are There Differences in Androgen Receptor Expression in Invasive Breast Cancer in African (Tanzanian) Population in Comparison With the Caucasian (Italian) Population? - Bravaccini, Sara; Ravaioli, Sara; Amadori, Dino; Scarpi, Emanuela; Puccetti, Maurizio; Rocca, Andrea; Tumedei, Maria Maddalena; Masalu, Nestory; Kahima, Jackson; Pangan, Akwilina; Faustine, Lucas; Farolfi, Alberto; et al. (Frontiers in Endocrinology, 2018)
Purpose: Androgen Receptor (AR) has been shown to have prognostic implication on breast cancer (BC). Data on the biological features of African BCs are poor. We decided for the first time to compare AR expression of Tanzanian and Italian BC patients. Patients and methods: Of the 69 consecutive patients seen at the Bugando Medical Center (Mwanza, Tanzania) from 2003 to 2010, who underwent resection of primary BC evaluable for estrogen receptor (ER), progesterone receptor (PgR), and HER2 only 65 were evaluable for AR by immunohistochemistry (IHC). Histopathological assessment and biomolecular determinations were performed at the Cancer Institute of Romagna (Istituto Scientifico Romagnolo per lo studio e la cura dei tumori (IRST) - IRCCS, Meldola, Italy). Caucasian BC patients were selected from an electronic database and matched (1:2 ratio) for year of diagnosis and age at diagnosis. Results: The median age of patients at diagnosis was 51 (range 29–83) years for Tanzanian and 53 (range 26–86) years for Italian patients. Tanzanian patients harbored tumors with lower AR expression than Italian patients according to the median percentage of immunopositive tumor cells (30% versus 80% p < 0.0001) and staining intensity (p = 0.0003). The proportion of AR negative patients was likewise higher among Tanzanian patients as regards both >1% and >10% cutoffs. AR positive BCs were higher in Luminal A and B tumors and decreased in triple negative and HER2-enriched tumors in Tanzanian population. Conclusions: AR loss could represent an unfavorable prognostic marker in the African population. The high frequency of triple negative tumors with high AR expression could open new perspectives of therapy for population in this low income country.